PMLK celebrates Ramadan Iftar with local communities - UMP, PNC (2019)
To appreciate the blessings of the holy fasting month of Ramadan, Universiti Malaysia Pahang (UMP) recently organized a breaking of fast – or popularly referred to its Arabic term as Iftar – in a congregation between its students and the surrounding local communities at the Gambang Mosque.